Le rôle de la Cour constitutionnelle dans la résolution des conflits entre la Constitution et le droit international - Sovdat, Jadranka (Pravnik, 2016)
The Slovenian Constitutional Court has the power to review the conformity of laws, other regulations and decisions of the courts not only with the Constitution but also with international law. With the powers invested in it, it ensures an effective execution of international law in Slovenia. Furthermore, it is responsible for resolving conflicts between international law and constitutional law. From that point of view, one can speak of three aspects of its role: firstly, the a priori constitutional review of treaties, secondly, the indirect constitutional review of treaties, and thirdly, the priority of the provisions of a treaty over the Constitution to establish a maximum protection of human rights. The Constitutional Court protects the Constitution by resolving the conflicts between the provisions of the Constitution and international law.
Keywords: človekove pravice; human rights; mednarodne pogodbe; mednarodno pravo; pravosodje; ustave; ustavna sodišča; ustavno pravo